Penanda Jamak Bahasa Arab dan Bahasa Indonesia dalam Kitab Fathul Qorib: (Sebuah Analisis Kontrastif) - Fatma Aslikhatul Amaliyah; Asep Maulana (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The plural contrastive analysis in the book of Fathul Qorib is very important because there are many plural formations and there are many errors in making plural forms in Arabic. This is due to a lack of understanding of easier ways to form plural words. This research has a research focus: (1) How plurals are formed in Arabic and Indonesian. (2) What are the similarities and differences in plural formation in Arabic and Indonesian. This research uses a type of research (library research), namely collecting data obtained through research on books, journals, books and websites. Data capture method. This research uses a cooperative descriptive method. The results of this research show that the plural in Arabic contained in the book of fathul qorib consists of the plural muannas salim 69 words, the plural mudzakar salim 79 words and the plural takir 192 words. Meanwhile, the plural in Indonesian contained in the translation of the book of Fathul Qorib consists of a total of 84 words reduplication, 4 partial reduplications, 2 words reduplication of other forms and 11 words affixing reduplication. The similarity in the formation of plurals in Arabic and Indonesian lies in the suffixes or addition of plural meanings. Meanwhile, the differences are: The plural in Indonesian does not recognize the form of tadzkir, is not used for absolutes, reduplication can be used as a plural formation and in Indonesian it does not recognize wazan or pattern while Arabic recognizes the form of tadzkir, there is a division between sensible and non-sensical or mulak, process reduplication cannot be used as a plural marker, whereas in Arabic wazan or the plural pattern takir can be used as a plural word formation.